Molecular Diversity of miR390-Guided Transacting siRNA Precursor Genes in Lower Land Plants: Experimental Approach and Bioinformatics Analysis. (11th October 2011) - Krasnikova, M. S.; Milyutina, I. A.; Bobrova, V. K.; Troitsky, A. V.; Solovyev, A. G.; Morozov, S. Y.
Abstract : Transacting siRNA loci (TAS3-like) of a particular plant species are usually represented by several gene families. PCR-based approach was used as a phylogenetic profiling tool to probe genomic DNA samples from representatives of evolutionary distant Bryophyta taxa, namely, class Bryopsida (subclasses Bryidae and Dicranidae) and class Sphagnopsida. We found relatives of all four Physcomitrella patens (subclass Funariidae) TAS3-like loci in subclasses Bryidae and Dicranidae. Only representatives of subclass Bryidae encoded TAS3-like genes belonging to P. patens TAS3a and TAS3d families. On the other hand, only the members of order Grimmiales (subclass Dicranidae) encoded gene relatives of P. patens TAS3c family. These data indicate that moss ta-siRNA families have been long conserved during land plant evolution. However, P. patens TAS3-like loci were detected neither in two Sphagnum species from the earliest diverged moss class Sphagnopsida, nor in the Selaginella kraussiana from the earliest extant tracheophyta lineage, Lycopodiopsida.